Análise comparativa de ferramentas de monitoramento, planejamento e gerenciamento de redes de computadores - PEREIRA, Rogerio Machado (2019)
Currently, it can be said that computer networks are becoming increasingly complex and larger, requiring special attention from organizations in aspects that did not previously exist. The high level of the number of devices required integration between them, making monitoring performance, operation and availability crucial points to be monitored in any company. When we think of monitoring, the main goal is to maximize the efficiency and productivity of one or more networks, and to keep them stable. When developing a plan to realize it, it is necessary to activate functions that allow the total control of the network and its services, with mechanisms of analysis and control of resources. Having a mapped and monitored environment is critical to the growth process of a business. It is already proven that with a well-planned IT environment, your business is more likely to work, even for companies where the main focus is not IT, because everyone now depends on the Internet and the services it provides. And for this it is necessary to use network management and monitoring tools, which were addressed during this work, then an analysis was done in scenarios of similar networks. This analysis had as objective to define which tool is the most appropriate, doing tests, defining the one that obtained the most performance management, all the tools used were tested in the demo version, they are; Netflow Analyzer, PRTG, WhtasUp Gold, Wireshark, then extracted and collected data from each tool and the results were analyzed and compared.